Morphological Variations and Morphometric Analysis of the Caudate Lobe of Liver: A Cadaveric Study - Prasad, Ram Jiban; Amgain, Kapil; Shah, Tirtha Narayan (Journal of Nepalgunj Medical College, 2021)
Introduction: The caudate lobe is most referred area of the liver radiologically. In cirrhosis, the right lobe exhibits relatively greater shrinkage, while the caudate lobe undergoes relative enlargement as it is the only segment which receives blood independently from left and right branches of portal veins. Aims: To assess the morphological variations and morphometric analysis of the caudate lobe of liver in the cadavers. Methods: This was a cross-sectional descriptive study conducted on 48 formalin fixed human liver specimens available in the gross anatomy laboratory of Department of Anatomy, National Medical College, Birgunj, Nepal. The caudate lobe of liver specimens was studied for morphological variations and different measurements were taken, and the result was presented in tables. Results: The caudate lobe showed a wide range of variations in shape. Caudate lobe was present in all 48 specimens of liver out of which, 15 specimens were rectangular (31.25%), 26 specimens were pyriform (54.16%) and 7 specimens were irregular (14.58%) respectively. In 6 liver specimens (12.50% of total number of liver specimens), there was vertical fissure that extended upwards from the lower border of caudate lobe was seen in 6 specimens (12.50%). Notch was present in 10 specimens (20.83%). Conclusion: The caudate lobe of the liver showed a great degree of variations and the most common shape was pyriform. The ratio of the transverse diameter of the caudate lobe to that of the right lobe of the liver (CT/RL) ratio was found to be 0.14.